Pengaruh Financial Distress dan Ukuran Perusahaan Terhadap Manajemen Laba dengan Kepemilikan Manajerial sebagai Variabel Moderasi - Bahiy Muhammad Tsaqif; Wulandari Agustiningsih (Jurnal Akuntansi dan Governance, 2021)
Exploration of the effect of financial distress and company size on earnings management with managerial ownership as a moderation variable into the purpose of this study. The use of quantitative and causal methods is the basis of this study supported by the population in the form of a state-owned enterprise company listed on the Indonesia Stock Exchange during the 2015-2019 and purposive sampling period as the basis for determining the sample. Multiple linear regression and moderated regression analysis are selected as data analysis techniques. Based on the results of statistical tests show that partially, financial distress and the size of the company have a significant negative effect on earnings management. Furthermore, Financial Distress moderated by managerial leadership has a significant negative effect on earnings management, as well as the size of the company moderated by managerial ownership has a significant positive effect on earnings management.